Increased Phosphorylation of Ser-Gln Sites on SUPPRESSOR OF GAMMA RESPONSE1 Strengthens the DNA Damage Response in Arabidopsis thaliana. Issue 12 (5th December 2017) - Yoshiyama, Kaoru Okamoto; Kaminoyama, Kaori; Sakamoto, Tomoaki; Kimura, Seisuke
Abstract : The number of phosphorylated sites on transcription factor SOG1 affects the strength of various DNA damage responses including DNA repair, replication arrest, cell death, and cell differentiation. Abstract: The Arabidopsis thaliana transcription factor SUPPRESSOR OF GAMMA RESPONSE1 (SOG1) regulates hundreds of genes in response to DNA damage, and this results in the activation of cell cycle arrest, DNA repair, endoreduplication, and programmed cell death. However, it is not clear how this single transcription factor regulates each of these pathways. We previously reported that phosphorylation of five Ser-Gln (SQ) motifs in the C-terminal region of SOG1 are required to activate downstream pathways. In this study, we introduced Ser-to-Ala (AQ) substitutions in these five SQ motifs to progressively eliminate them and then we examined the effects on DNA damage responses. We found that all SQs are required for the full activation of SOG1 and that the expression level of most downstream genes changed incrementally depending on the number of phosphorylated SQ sites. Genes involved in DNA repair and cell cycle progression underwent stepwise activation and inhibition respectively as the number of phosphorylated SQ sites increased. Also, inhibition of DNA synthesis, programmed cell death, and cell differentiation were incrementally induced as the number of phosphorylated SQ sites increased. These results show that the extent of SQ phosphorylation in SOG1 regulates gene expression levels and determines the strength of DNA damage responses.